Geography and the Market for CEOs - Yonker, Scott E. (Management Science, 2017)
I examine the role of geography in the market for CEOs and find that firms hire locally five times more often than expected if geography were irrelevant to the matching process. This local matching bias is widespread and exists even among the largest U.S. firms. Tests reveal that both labor supply and demand influence local matching. Compensation and unforced turnover are lower for local than for nonlocal CEOs, and the compensation of local CEOs depends on local labor market factors, unlike that of nonlocal CEOs. These findings suggest the presence of market segmentation and contrast with much of the prior literature, which explicitly or implicitly assumes a single national market. This paper was accepted by Lauren Cohen, finance.